Between Parks and Reserves: the process of creation and participation in the management in state Conservation Units of Amazonas (Terr@ Plural, 2022)
This study analyzes issues related to the creation and the process of participation of the local population in the management of three state Conservation Units (UCs) in Amazonas. The data were collected in two sustainable use units, Sustainable Development Reserve (RDS) of Uatumã and Juma, and in the Rio Negro Setor Norte State Park (PAREST) in 2011 and 2012. Field surveys were carried out, supported by open interviews and semi-structured, direct, and participant observation on the process of creating the Units and the participation of local populations in the management of UCs. Our data show that, in some cases, the subjects act in the management through a “participative management”, but not participating, as for example in the construction of the management plans, in which the local populations are involved, through “participation passive”, as a source of information or even for the approval of proposals, but without active participation in the process of creating and managing the Unit.
Keywords: Participation; Local population; Amazonia